TAṬWĪR MAHĀRĀT AL-ITTIṢĀL LADĀ MUTA‘ALLIMĪ AL-LUGAH AL-‘ARABIYYAH LUGATAN ṠĀNIYAH FĪ AL-TA‘LĪM AL-QĀIM ‘ALA AN-NAWĀTIJ - Rivensky, Rizka; Nadwah Daud; Nik Hanan Mustapha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Outcome-based education (OBE) clearly puts the ‘learning outcomes’ that match the needs of profession atmosphere over the ages. Meanwhile, oral communication is one of the language skills that have been of interest to most professional fields out there. The International Islamic University Malaysia has been enduring OBE for years. An educational system is one of the predisposing and exciting elements for developing skills nonetheless language skills to some extent, as it may prepare the learners to practicing and developing language skills among themselves. The researchers conducted this study on 234 learners, by using a set of aquestionnaire adopted from past studies to look intolearners’ viewstowards development of oral communication skill among them through certain learning activities while they endured OBE. The study concluded that all these activities benefited the learners in developing the skill in many aspects that were clarified in the study result.